Angiotensin type 1 receptor autoantibody from preeclamptic patients induces human fetoplacental vasoconstriction12. Issue 1 (4th October 2012) - Zhang, Suli; Zheng, Ronghua; Yang, Lihong; Zhang, Xi; Zuo, Lin; Yang, Xiaoli; Bai, Kehua; Song, Li; Tian, Jue; Yang, Jie; Liu, Huirong
Abstract Increased vascular resistance in the fetoplacental circulation is a characteristic of preeclampsia. However, the potential molecular mechanisms of this condition remain obscure. The current study aimed to determine the direct effect of the peptide antigen corresponding to the second extracellular loop of the angiotensin II type 1 receptor (AT1R‐ECII) activating autoantibody (AT1‐AA), a novel risk factor in preeclamptic patients, on fetoplacental villus stem blood vessels. Immunohistochemistry revealed that AT1 receptors were localized in the veins and arteries of human placental villi. Among 58 serum samples from preeclamptic patients, 28 (48.28%) were proved AT1‐AA‐positive by enzyme‐linked immunosorbent assay [P < 0.01 vs. 2/51 (3.92%) in the normal pregnancy group]. Total IgGs purified from AT1‐AA‐positive patients' sera (AT1‐AA‐IgGs) were added to isolated normal human placental blood vessels. The IgG significantly constricted both the villus veins and arteries in a dose‐dependent manner in vitro, which could be blocked by the peptide corresponding to the human AT1R‐ECII, anti‐human IgG or the AT1 receptor antagonist losartan. Additionally, the venous constriction induced by AT1‐AA‐IgGs remained unchanged even at the end of the experiment (about half an hour), but the vasoconstriction caused by the AT1 receptor agonist angiotensin II underwent desensitization within three minutes. Collectively, our results demonstrated that AT1‐AA in preeclamptic sera can directly constrict fetoplacental villus blood vessels without desensitization via the AT1 receptor in vitro, which might contribute to poor fetoplacental perfusion in preeclampsia. J. Cell. Physiol. 228: 142–148, 2013. © 2012 Wiley Periodicals, Inc.